Meniscal Surgery: Risk of Radiographic Joint Space Narrowing Progression and Subsequent Knee Replacement-Data from the Osteoarthritis Initiative - Zikria, Bashir; Hafezi-Nejad, Nima; Roemer, Frank; Guermazi, Ali; Demehri, Shadpour (Radiology, 2017)
Purpose To investigate the risk of radiographic joint space narrowing (JSN) progression evaluated in subjects with and those without underlying osteoarthritis at baseline and knee replacement (KR) associated with meniscal surgery in subjects with and those without a reported history of preceding knee trauma. Materials and Methods The HIPAA-compliant protocol was approved by the institutional review boards of the participating centers. Written informed consent was obtained from all participants. Subjects who underwent meniscal surgery with a preceding knee trauma at baseline (n = 564) and those without (n = 147) were drawn from the Osteoarthritis Initiative cohort (n = 4796). Radiographic JSN progression was evaluated by using Osteoarthritis Research Society International grading (progression in 1st-, 2nd-, 3rd-, 4th-, 6th-, or 8th-year radiographic findings compared with baseline). KR was assessed up to the 9th year of study (days passed from inclusion to KR or last follow-up). Cox hazard analysis was used to extract the adjusted hazard ratios (HRs) with adjustments for baseline age, sex, body mass index, physical activity, symptoms, and radiographic osteoarthritis features (Kellgren and Lawrence [KL] grade). Results Meniscal surgery with a history of preceding knee trauma was not associated with radiographic progression of JSN (adjusted HR, 0.91 [95% confidence interval CI: 0.78, 1.07]) or KR (adjusted HR, 1.02 [95% CI: 0.79, 1.34]; P = .854). However, meniscal surgery without a history of preceding knee trauma was associated with radiographic progression of JSN (adjusted HR, 1.27 [95% CI: 1.00, 1.63]) and KR (adjusted HR, 2.09 [95% CI: 1.52, 2.89]; P < .001). Additionally, there was a higher risk of KR in subjects with radiographic KL grade of less than 2 (adjusted HR, 6.97 [95% CI: 3.56, 13.64]; P < .001) at baseline in comparison with KL grade of at least 2 (adjusted HR, 1.76 [95% CI: 1.22, 2.54]; P < .05). Conclusion In contrast to subjects without a reported preceding trauma, meniscal surgery is not independently associated with increased risk of radiographic JSN progression and KR in patients with a reported preceding trauma. © RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:14732